2022
DOI: 10.3389/fbioe.2022.815393
|View full text |Cite
|
Sign up to set email alerts
|

Decontamination of High-Efficiency Mask Filters From Respiratory Pathogens Including SARS-CoV-2 by Non-thermal Plasma

Abstract: The current pandemic resulted in a rapidly increasing demand for personal protective equipment (PPE) initially leading to severe shortages of these items. Hence, during an unexpected and fast virus spread, the possibility of reusing highly efficient protective equipment could provide a viable solution for keeping both healthcare professionals and the general public equipped and protected. This requires an efficient decontamination technique that preserves functionality of the sensitive materials used for PPE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Other studies have reported viral inactivation with different NTP devices but not without drawbacks . The need of vacuum systems, feed gases, , high gas temperatures that can damage the materials, , or very long treatment times make those devices unsuitable for routine hospital use. Moreover, gas-fed NTP, such as plasma jets, could present additional health risks, as the constant gas flow could blow microdroplets that carry viruses and other contaminating particles into the surrounding environment, thus further spreading its reach.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported viral inactivation with different NTP devices but not without drawbacks . The need of vacuum systems, feed gases, , high gas temperatures that can damage the materials, , or very long treatment times make those devices unsuitable for routine hospital use. Moreover, gas-fed NTP, such as plasma jets, could present additional health risks, as the constant gas flow could blow microdroplets that carry viruses and other contaminating particles into the surrounding environment, thus further spreading its reach.…”
Section: Discussionmentioning
confidence: 99%
“…They vary in the structure of electrodes, the type of power sources, a pulse/continual regime and the composition of the used atmosphere. Thanks to these techniques, NTP was successfully employed in a wide range of applications, starting from rendering surfaces hydrophilic [9], their decontamination [10], antifungal and conservation treatment of food and seeds causing extension of their shelf life [8,[11][12][13] and green technology [14] for the effective disinfection of respirators and other medical equipment [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…NTP exhibits antimicrobial 2 7 and antiviral effects 8 , 9 , and its applications have been the subject of intensive research in recent decades 6 , 10 12 . As NTP is typically generated in ambient air, the largest proportion of microbicidal and virucidal agents are reactive oxygen species (ROS) and reactive nitrogen species (RNS) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…This topic became of relevance in reported NTP applications for the decontamination of protective equipment during the pandemic of COVID-19. Several studies were published at this time of lack of protective equipment, mainly face masks and respirators 8 , 9 , 18 20 . In our previous study Obrová et al 8 , we reported that NTP can be advantageously used for the decontamination of respiratory P3 R filters without affecting their filtration capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation